Description of the final instar larvae of Erythrodiplax atroterminata Ris and E. corallina (Brauer) (Odonata: Libellulidae) - Garré, Analía (2008)
The last instar larva of Erythrodiplax atroterminata and E. corallina are described and illustrated, based on reared specimens from Argentina. A comparative analysis of all hitherto known larvae from Argentina is provided.